Learning of Shot-Put for Class VIII Elementary School - Kurniawan, Rizkei (LPPM Universitas Primagraha, 2020)
The general objective of this research is to improve the students learning outcomes through the learning of Shot-Put by using Somatis Approach. In addition, this research is conducted to obtain in-depth information about the application of Shot-Put by using Somatis Approach. The design of this study is Action Research. The subjects in this study are 25 students of the eight grade at SMP Negeri 2 Gebang. This study is conducted in two sessions of two cycles. Each cycle consists of three sessisons. The first cycle shows that through the action the students can motivate themselves. From this cycle the result is 68% and it means completed. In the second cycle as the reflection of first cycle also shows that the action motivated the students. The result of the second cycle is 88% and it means completed. Based on the results of this study it can be concluded that: (1) Learning Shot-Put by using Somatis Approach increases the students learning outcomes, (2) Learning Shot-Put by using Somatis Approach motivates the students and make the students active in participating the learning process